Intelligence Oversight in Indonesia: The Dilemma of Human Rights and National Security - Putra, Satria Rangga (Darma Cendika Catholic University, 2025)
Democratic oversight of intelligence is an instrument to ensure that intelligence activities uphold the principles of human rights and protect liberties of civil society. Based on Law Number 17 of 2011 concerning State Intelligence, oversight is divided into two, internal and external. Internally it is carried out by each state intelligence administrator and externally through the Intelligence Oversight Team of House of Representative. Intelligence oversight has several problems, ranging from regulatory factors, conflicts of interest (political factors) to the weak capacity of oversight actors in assessing alleged violations and considerations of political stability and national security. This paper attempts to constructively analyze the regulation of intelligence oversight in Indonesia and various contemporary problems that surround it. This paper uses a normative juridical research method, with a concept and legislation approach. This research found that the attachment of oversight actors to the limits of intelligence secrets makes it all in a dilemma so that it is impossible to open up allegations of human rights violations of state intelligence to the public holistically. The existence of conflict of interest, void and unclear regulations, until threats to the members of State Intelligence Oversight Team is also a separate inhibiting factor in conducting oversight.